Molecular and chromosomal mechanisms of resistance to imatinib (STI571) therapy - Hochhaus, Andreas; Kreil, Sebastian; Corbin, A. S.; La Rosée, Paul; Müller, Martin Christian; Lahaye, T.; Hanfstein, Benjamin; Schoch, C.; Cross, N. C. P.; Berger, Ute; Gschaidmeier, Harald; Druker, B. J.; et al. (Leukemia, 2002)
Selective inhibition of the BCR-ABL tyrosine kinase by imatinib (STI571, Glivec/Gleevec) is a promising new therapeutic strategy in patients with chronic myelogenous leukemia (CML). Despite significant hematologic and cytogenetic responses, resistance occurs, particularly in patients with advanced disease. We sought to determine the underlying mechanisms. Sixty-six patients with CML in myeloid blast crisis (n = 33), lymphoid blast crisis (n = 2), accelerated phase (n = 16), chronic phase (n = 13), and BCR-ABL-positive acute lymphoblastic leukemia (n = 2) resistant to imatinib were investigated. Median duration of imatinib therapy was 148 days (range 6-882). Patients were evaluated for genomic amplification of BCR-ABL, overexpression of BCR-ABL transcripts, clonal karyotypic evolution, and mutations of the imatinib binding site in the BCR-ABL tyrosine kinase domain. Results were as follows: (1) Median levels of BCR-ABL transcripts, were not significantly changed at the time of resistance but 7/55 patients showed a >10-fold increase in BCR-ABL levels; (2) genomic amplification of BCR-ABL was found in 2/32 patients evaluated by fluorescence in situ hybridization; (3) additional chromosomal aberrations were observed in 19/36 patients; (4) point mutations of the ABL tyrosine kinase domain resulting in reactivation of the BCR-ABL tyrosine kinase were detected in 23/66 patients. In conclusion, although the heterogeneous development of imatinib resistance is challenging, the fact that BCR-ABL is active in many resistant patients suggests that the chimeric oncoprotein remains a good therapeutic target. However, patients with clonal evolution are more likely to have BCR-ABL-independent mechanisms of resistance. The observations warrant trials combining imatinib with other agents.
Gesehen am 16.05.2022